Long-term Compliance with Oral 5-aminosalicylic Acid Therapy and Risk of Disease Recurrence in Patients with Ulcerative Colitis: A Population-based Cohort Study. Issue 4 (April 2016) - Prosberg, Michelle V.; Vester-Andersen, Marianne K.; Andersson, Mikael; Jess, Tine; Andersen, Jon T.; Vind, Ida; Bendtsen, Flemming
Abstract : Background: Noncompliance to long-term medical therapy is a well-known problem among patients treated for ulcerative colitis, but studies of long-term consequences in unselected patients are lacking. The authors aimed to determine the risk of recurrence according to long-term compliance with oral 5-aminosalicylic acid among unselected patients with ulcerative colitis. Methods: The authors conducted a 7-year follow-up study of a population-based inception cohort of 243 Danish patients with ulcerative colitis diagnosed from 2003 to 2004. Compliance was defined as consumption of ≥80% of prescribed oral 5-aminosalicylic acid. Data were collected from medical records and the Danish National Prescription Database. They performed Cox regression analysis with adjustments for demographic and clinical characteristics to examine risk of recurrence (defined by increased use of oral 5-Aminosalicylic Acid, other additional treatment, or colectomy) in compliant versus noncompliant patients. Results: In total, 182 patients (75%) experienced at least 1 recurrence during follow-up. For the first year after diagnosis, risk of recurrence did not differ significantly between compliant and noncompliant patients. For 1 to 3 years (hazard ratio: 0.46, 95% CI, 0.33–0.63) and 3 to 8 years (hazard ratio: 0.42, 95% CI, 0.32–0.55) after diagnosis, risk of recurrence was significantly decreased among noncompliant patients compared with that of compliant patients. Conclusions: This unselected cohort study revealed a reverse association between compliance and recurrence of ulcerative colitis. This is unlikely to be explained by severe confounding because the authors were able to adjust for several demographic and clinical factors. Results may instead reflect that patients during recurrence-free periods through self-management choose not to take their medication. Abstract : Article first published online 28 January 2016.